EFFECT FAMILY OWNERSHIP ON FINANCIAL PERFORMANCE WITH BUSINESS STRATEGY AS MODERATION AND AGENCY COST AS MEDIATION IN NON-FINANCIAL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2016-2018 - M. Budi Widiyo Iryanto; Sisilia Devina Permatasari; Abdulah Rakhman (International Journal of Social Science, 2022)
This research aims to analyze some hypotheses provided. First, the effect of family ownership on financial performance. Second, the effect of family ownership on agency cost. Third, the effect of agency cost on financial performance. Forth, the effect of business strategies in moderating the relationship between family ownership and financial performance. Lastly, the effect of agency cost as a moderating variable between family ownership relationships and financial performance. The object of this research is to analyze the non-financial companies listed on the Indonesia Stock Exchange by looking at the Annual Reports in 2016-2018. The sampling method is by using purposive sampling, which obtained 117 of company or 351 units of analysis. Those sample tested by PLS-SEM through Smart PLS Version 3. The results of this research are found in the following sentences. First, family ownership has a direct and having significant positive effect on financial performance. Second, family ownership has a positive but not having significant effect on agency cost. Third, agency cost has a negative and having significant effect on financial performance. Forth, business strategy is moderating the relationship between family ownership and financial performance. Lastly, the indirectly agency cost is not moderating the relationship between family ownership and financial performance